강제동요 시험을 이용한 모형 계류삭의 동적 응답 연구 - 조석규(SEOK-KYU CHO); 홍사영(SA-YOUNG HONG); 홍섭(SUP HONG); 김현조(HYUN-JOE KIM) (Han-guk haeyang gonghak hoeji (Online), 2005)
A series of forced oscillation tests on a model mooring chain was carried out to investigate dynamic tension characteristics. The model test was conducted at two different water depths to gather basic data for a 'truncated mooring test' and 'hybrid mooring test'. The truncated and hybrid mooring tests are important for overcoming the limitation of water depth that existed in previous model tests. The resultant tension RAO provides a good possibility of approximation of dynamic tension by equivalent weight adjustment for different water depths. Because the hybrid mooring test is an adequate combination of model test and simulation, an accurate simulation model for the mooring system is essential. The simulation results show good agreement with model test results.